Child Growth and Development - Paris, Jennifer; Ricardo, Antoinette; Rymond, Dawn; Johnson, Alexa; Open Textbook Library (Open Textbook Library, 2018)
Welcome to Child Growth and Development. This text is a presentation of how and why children grow, develop, and learn. We will look at how we change physically over time from conception through adolescence. We examine cognitive change, or how our ability to think and remember changes over the first 20 years or so of life. And we will look at how our emotions, psychological state, and social relationships change throughout childhood and adolescence. This book is also available as an adaptable Word file.
Chapter 1: Introduction to Child Development -- Chapter 2: Conception, Heredity, & Prenatal Development -- Chapter 3: Birth and the Newborn -- Chapter 4: Physical Development in Infancy & Toddlerhood -- Chapter 5: Cognitive Development in Infancy and Toddlerhood -- Chapter 6: Social and Emotional Development in Infancy and Toddlerhood -- Chapter 7: Physical Development in Early Childhood -- Chapter 8: Cognitive Development in Early Childhood -- Chapter 9: Social Emotional Development in Early Childhood -- Chapter 10: Middle Childhood - Physical Development -- Chapter 11: Middle Childhood - Cognitive Development -- Chapter 12: Middle Childhood - Social Emotional Development -- Chapter 13: Adolescence - Physical Development -- Chapter 14: Adolescence - Cognitive Development -- Chapter 15: Adolescence - Social Emotional Development
In English.
Description based on online resource
Keywords: Psychology -- Textbooks